2003
DOI: 10.4049/jimmunol.171.1.398
|View full text |Cite
|
Sign up to set email alerts
|

A Site on Laminin α5, AQARSAASKVKVSMKF, Induces Inflammatory Cell Production of Matrix Metalloproteinase-9 and Chemotaxis

Abstract: Several peptide sequences in laminin α1, the α-chain of laminin (Ln)-1, mediate biological responses in vitro, but Ln-1 is rare in vivo. Since Ln-5 and Ln-10, which contain the α3 and α5 chains, respectively, are the most prominent laminin heterotrimers in normal adult tissues and few functional domains in other laminin chains have been identified, we are investigating the α3 and α5 chains for biological activities. Incubation of mouse macrophages with the laminin α5 peptide AQARSAASKVKVSMKF resulted in marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 64 publications
3
51
0
Order By: Relevance
“…It is known that neutrophil proliferation is enhanced by fibrinogen 31 and survival increased by fibronectin and laminin 32. Laminin enhances protease release from neutrophils and neutrophil chemotaxis 33 potentiating inflammatory cell movement. The current study findings suggest tumstatin has the potential to create an anti‐inflammatory microenvironment, which inhibits neutrophils in the airway tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neutrophil proliferation is enhanced by fibrinogen 31 and survival increased by fibronectin and laminin 32. Laminin enhances protease release from neutrophils and neutrophil chemotaxis 33 potentiating inflammatory cell movement. The current study findings suggest tumstatin has the potential to create an anti‐inflammatory microenvironment, which inhibits neutrophils in the airway tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which NE may mediate neutrophil transmigration and/or BM remodeling, directly or indirectly, is at present unclear, especially in the light of the broad substrate specifi city of NE (41). It is of course highly probable that NE may have indirect roles in mediating neutrophil transmigration, for example, via activation of other leukocyte proteases such as MMP-9 (17) or generation of chemotactic fragments by selective cleavage of BM constituents (42)(43)(44) or cellular receptors. However, NE may also play a direct role in mediating neutrophil transmigration, possibly via cleavage of BM constituents (17,40).…”
Section: Discussionmentioning
confidence: 99%
“…Because laminin ␣5 is widely expressed in fetal and adult tissues, we are characterizing the function of specific domains of the laminin ␣5 chain. We previously reported that the laminin ␣5 peptide, AQARSAASKVKVSMKF, induces matrix metalloproteinase-9 (MMP-9) production and is chemotactic for leukocytes in vitro and in vivo (8). Furthermore, our data indicated that AQARSAASKVKVSMKF is cryptic in the intact laminin-10 molecule.…”
mentioning
confidence: 58%
“…Although the role of ECM in affecting inflammatory cell functions has been examined, the predominant focus has been the effect of ECM components on adhesion, migration (5)(6)(7)(8)(9), and proteinase production (5)(6)(7)(8)(9)(10). Little is known about the effects of ECM components on cytokine production.…”
mentioning
confidence: 99%